The influence of sand surface on the kinematics of volleyball spike jumps - Tilp, M.; Wagner, H.; Müller, E. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Several types of sports, like soccer, European handball, and volleyball have expanded their classical fields of activity from indoor surfaces made of wood or synthetic and outdoor turf to sand surfaces. Previous studies reported differences in both body mechanics and energy demands during several types of movement on sand or similar compliant surfaces compared to hard surfaces. Therefore, we investigated the differences in kinematics during spike jumps performed on indoor or sand surface (Tilp et al., 2008).